On Integrating Unmanned Aircraft Systems into the National Airspace System - Dalamagkidis, Konstantinos (Springer, 2017)
This book presents, in a comprehensive way, current unmanned aviation regulation, airworthiness certification, special aircraft categories, pilot certification, federal aviation requirements, operation rules, airspace classes and regulation development models.